Instruments Measuring Self-Care and Self-Management of Chronic Conditions by Community-Dwelling Older Adults: A Scoping Review. (July 2023) - Lawless, Michael T.; Tieu, Matthew; Chan, Raymond J.; Hendriks, Jeroen M.; Kitson, Alison
Given the high prevalence of chronic conditions and multimorbidity in older adults, there is a need to better conceptualize and measure self-care and self-management to promote a person-centered approach. This scoping review aimed to identify and map instruments measuring self-care and self-management of chronic conditions by older adults. We searched six electronic databases, charted data from the studies and tools and reported the results in accordance with the PRISMA-ScR guidelines. A total of 107 articles (103 studies) containing 40 tools were included in the review. There was substantial variation in the tools in terms of their aims and scope, structure, theoretical foundations, how they were developed, and the settings in which they have been used. The quantity of tools demonstrates the importance of assessing self-care and self-management. Consideration of the purpose, scope, and theoretical foundation should guide decisions about tools suitable for use in research and clinical practice.